2014
DOI: 10.1002/tkm2.1008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yokukansan on sleep disturbance in a rat model of cerebrovascular dementia

Abstract: Aim: Symptoms of dementia are classified into cognitive dysfunction and behavioral and psychological symptoms of dementia, including sleep disturbance. Yokukansan (YKS) is effective for sleep disturbance in patients with dementia, but the mechanisms are still unclear. In this study, we evaluated sleep disturbance in rats with cerebral ischemia. We investigated the effect of YKS on sleep disturbance in cerebral ischemia-treated rats. Methods: Cerebral ischemia was induced by twice occluding both of the common c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Yokukansan has also been shown to reverse the shortening of sleep time induced by pentobarbital injection in socially isolated mice ( Egashira et al, 2011 ). Recently, using electroencephalography and electromyography, Nagao et al (2014) investigated the effect of oral administration of YKS on sleep disturbance in a rat model of cerebrovascular dementia. Rats with cerebral ischemia had a higher total wakefulness time and lower total non-rapid eye movement sleep, so it was concluded that sleep disturbances were ameliorated by YKS.…”
Section: Psychopharmacological Effects Of Yksmentioning
confidence: 99%
“…Yokukansan has also been shown to reverse the shortening of sleep time induced by pentobarbital injection in socially isolated mice ( Egashira et al, 2011 ). Recently, using electroencephalography and electromyography, Nagao et al (2014) investigated the effect of oral administration of YKS on sleep disturbance in a rat model of cerebrovascular dementia. Rats with cerebral ischemia had a higher total wakefulness time and lower total non-rapid eye movement sleep, so it was concluded that sleep disturbances were ameliorated by YKS.…”
Section: Psychopharmacological Effects Of Yksmentioning
confidence: 99%
“… and Nagao et al . . Electrodes for EEG and EMG recording were implanted after the guide cannulas were implanted.…”
Section: Methodsmentioning
confidence: 99%
“…Nagao et al . reported that cerebral ischemia induced longer total wakefulness time and shorter total non‐rapid eye movement (non‐REM) sleep time in rats during the light phase, while repeated treatment with YKS improved these changes, suggesting a positive effect of YKS on sleep disturbance . Finally, Ogawa et al .…”
Section: Behavioral Effectsmentioning
confidence: 95%